Relationship between ocular and computed tomography findings in patients with spina bifida - Temizsoylu, Onur; Koçkar, Alev; Alataş, İbrahim and Canaz, Hüseyin and Şengül, Elvan Alper and Yüzbaşıoğlu, Erdal (The European Research Journal, 2020)
Objectives: Spina bifida is one of the most common congenital diseases in Turkey and around the world. Despite the developing diagnostic and therapeutic methods, abnormal ocular characteristicsin spina bifida patients are still quite common. We investigated the ocular characteristics of spina bifida patients with and without hydrocephalus. Methods: We included 37 patients who were previously referred to the Istanbul Bilim University, Department of Ophthalmology and already had computed tomography (CT) scans. We retrospectively investigated the patients’ ophthalmologic findings (refractive errors, strabismus, and optic disc characteristics) and used their recent CT images to measure the Evans ratios (ERs), which indirectly reflect the grade of hydrocephalus. The patients were divided into three groups according to their ERs (ER ≤ 0.3, 0.3-0.5, and ≥ 0.5), and then the ocular characteristics of these groups were compared. In addition, the patients were divided into three groups according to their ages ( ≤ 1 year, 1-3 years, and ≥ 3 years), and the ERs and rates of refraction defects in these groups were compared. Results: There was no relationship between specific ocular characteristics and ER or between age and ER. However, refraction errors were observed more fr equently as patient age increased. Conclusions: The degree of hydrocephalus does not affect the ocular characteristics of patients with spina bifida, but emmetropization may be deteriorated in these patients.